METHODOLOGICAL PRINCIPLES OF TAX AUDITS (Academicia Globe: Inderscience Research, 2023)
In this article, research was carried out on ways to improve the activity of tax authorities and assess their efficiency in tax control in textile enterprises, and conclusions and proposals were formed within the framework of the research.